2021
DOI: 10.1111/ejss.13105
|View full text |Cite
|
Sign up to set email alerts
|

Greater, but not necessarily better: The influence of biochar on soil hydraulic properties

Abstract: Biochar is recommended as a soil amendment for its positive influence on soil hydrological properties, which results in improved soil fertility and crop yield. Much research in the last decade has been conducted in field and laboratory conditions on the effect of biochar on the hydraulic properties of soil. However, reported results in the literature are substantially inconsistent. Here we performed a meta‐analysis to capture the variations in change in hydraulic properties of arable soils after application of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 59 publications
1
14
0
Order By: Relevance
“…For instance, Omondi et al (2016) found that the biochar's effect of medium pyrolysis temperature on total porosity was better than that at low pyrolysis, while Edeh et al (2020) reported that pyrolysis temperature had no significant effect on the response of SP to biochar application when taking 500°C as the boundary between high and low pyrolysis temperature. The disparate database could also be a cause of such difference because experimental conditions had an influence on the results (Edeh et al, 2020; Omondi et al, 2016; Rabbi et al, 2021; Razzaghi et al, 2020), and our database only includes field researches.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…For instance, Omondi et al (2016) found that the biochar's effect of medium pyrolysis temperature on total porosity was better than that at low pyrolysis, while Edeh et al (2020) reported that pyrolysis temperature had no significant effect on the response of SP to biochar application when taking 500°C as the boundary between high and low pyrolysis temperature. The disparate database could also be a cause of such difference because experimental conditions had an influence on the results (Edeh et al, 2020; Omondi et al, 2016; Rabbi et al, 2021; Razzaghi et al, 2020), and our database only includes field researches.…”
Section: Discussionmentioning
confidence: 99%
“…Lots of meta‐analyses have focused on the effects of biochar application on crop yield, soil basic properties, and greenhouse gas emissions (Crane‐Droesch et al, 2013; Jeffery et al, 2011; Liu et al, 2013; Ye et al, 2020). However, there have been limited meta‐analyses to investigate the response of soil hydrological properties to biochar application though inconsistency of results was presented (Edeh et al, 2020; Omondi et al, 2016; Rabbi et al, 2021; Razzaghi et al, 2020). Razzaghi et al (2020) and Omondi et al (2016) reported that biochar could reduce soil bulk density (BD) by around 7%, but Edeh et al (2020) found that biochar had no significant effect on soil BD.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The aged biochars may also have a detrimental effect on the growth of earthworms and/or fungi (Anyanwu et al., 2018), thereby affecting soil health and nutrient availability. Despite the above, a recent meta‐analysis study reported that application of biochar @ >50 t/ha would be required for improvement of hydraulic properties of sandy soils under laboratory conditions (Rabbi et al., 2021). The authors suggested that the application of such a huge amount would involve high costs during biochar production and would require further research I producing effective biochar with optimum porosity, surface area, and hydrophilic properties.…”
Section: Impact Of Organic Amendments and Pgpr On Crop Productivity Under Drought Stressmentioning
confidence: 99%